The Study of Jochid Genealogy according to Rashid al-Din’s “Shuab-i Pandjghana” - I.M. Mirgaleev; Ch.I. Khamidova (Золотоордынское обозрение)
The authors of the present study describe the Rashid al-Din’s work “Shuab-i pandjghana” obtained from the archives of the Topkapi Palace Museum in Istanbul and containing genealogies of the reigning dynasties of the “five peoples”. The article contains a brief description of the previous study of this important Rashid al-Din’s work. The authors also analyze the information on the “Shuab-i pandjghana” contained in the A.P.Grigoryev’s study. The authors present their own version about how “Shuab-i pandjghana” got to Anatolia, how the latest version of Rashid al-Din’s work corresponds to his famous composition “Jami al-tawarikh”. The study contains comparison of the information given in two Rashid al-Din’s works – “Jami al-Tawarikh” and “Shuab-i pandjghana”, which shows the difference between them. The authors believe that the information gathered for “Jami al-tawarikh” was the main source, but then some additions and corrections were made. The authors of the article also make an attempt to determine the date when this genealogy was created. They think that this genealogy was compiled later than it is considered to be based on the information given in the preface of the “Shuab-i pandzhgana” and the genealogies. Also one of the arguments is that while writing such a large-scale work as “Jami al-tawarikh” it is difficult to prepare other complex work as genealogies. In the authors’ opinion the fact that the manuscript nowadays is known only in one copy counts in favor of the point of view that the work refers to the end of author’s life. According to the article, by using “Shuab-i pandjghana” one can both accurately trace the genealogy of the Batuid rulers in the Golden Horde and also have an excellent background information for understanding the genealogies of other Jochid branches.